Strategi Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kualitas Kinerja Karyawan Di PT. PLN Rayon Rungkut - Alvin Indrawan Putra; Dodit Cahyo Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study analyzes the HR development strategy at PT. PLN Rayon Rungkut and its impact on employee performance. Using a descriptive qualitative method, this study found that PT. PLN Rayon Rungkut has successfully implemented effective training such as On the Job Training (OJT) and Off the Job Training (Off-JT), which improves employee skills and knowledge. This strategy improves productivity, efficiency, adaptation to change, satisfaction, employee retention, and positive work culture. In conclusion, the HR development strategy at PT. PLN Rayon Rungkut has improved employee performance and has a positive impact on the company. This strategy must continue to be implemented and adjusted to the needs of the labor market to ensure employee performance remains optimal.